Deletion of MicroRNA-144/451 Cluster Aggravated Brain Injury in Intracerebral Hemorrhage Mice by Targeting 14-3-3ζ - Wang, Xiaohong; Hong, Yin; Wu, Lei; Duan, Xiaochun; Hu, Yue; Sun, Yongan; Wei, Yanqiu; Dong, Zhen; Wu, Chenghao; Yu, Duonan; Xu, Jun (Frontiers in Neurology, 2021)
The present study aimed to investigate the role of microRNA-144/451cluster (miR-144/451) in intracerebral hemorrhage (ICH), and to further assess its underlying mechanism. An ICH mice model was established and a simple miR-144/451 gene knockout (KO) mouse model was applied in the current study. 3 days following ICH induction, neurological function, brain water content were measured. Levels of pro-inflammatory cytokines including tumor necrosis factor-α (TNF-α) and interleukin-1β (IL-1β) and certain biomarkers of oxidative stress were also determined in current study. The results of the current study revealed that miR-451 significantly downregulated in ICH mice, while miR-144 showed no significant change. Knockout of miR-144/451 cluster exacerbated the neurological deficits and brain edema in ICH mice. Further analyses demonstrated that knockout of miR-144/451 cluster significantly promoted TNF-α and IL-1β secretion and oxidative stress in ICH mice. In addition, it was revealed that the depletion of miR-144/451 repressed the miR-451-14-3-3ζ-FoxO3 regulatory axis in ICH mice. In conclusion, these data indicated that miR-144/451 may protect ICH mice against neuroinflammation and oxidative stress by targeting miR-451-14-3-3ζ-FoxO3 pathway.